2018
DOI: 10.1038/s12276-018-0184-0
|View full text |Cite
|
Sign up to set email alerts
|

FAM46B inhibits cell proliferation and cell cycle progression in prostate cancer through ubiquitination of β-catenin

Abstract: FAM46B is a member of the family with sequence similarity 46. Little is known about the expression and functional role(s) of FAM46B in prostate cancer (PC). In this study, the expression of FAM46B expression in The Cancer Genome Atlas, GSE55945, and an independent hospital database was measured by bioinformatics and real-time PCR analysis. After PC cells were transfected with siRNA or a recombinant vector in the absence or presence of a β-catenin signaling inhibitor (XAV-939), the expression levels of FAM46B, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 37 publications
(43 reference statements)
0
21
0
Order By: Relevance
“…FAM46A expression was increased in glioma patients and cisplatin-resistant gastric cancer cell lines and associated with pathological grade, overall survival and progressionfree survival of glioma patients [6,7]. FAM46B expression was decreased in prostate cancer patients and inhibited cell proliferation and cell cycle progression through ubiquitination of β-catenin [8]. Deletions of FAM46C have been found in a few cancers, including multiple myeloma [9], gastric cancer [10] and myeloma [11], and to be associated with a shorter overall survival.…”
Section: Introductionmentioning
confidence: 99%
“…FAM46A expression was increased in glioma patients and cisplatin-resistant gastric cancer cell lines and associated with pathological grade, overall survival and progressionfree survival of glioma patients [6,7]. FAM46B expression was decreased in prostate cancer patients and inhibited cell proliferation and cell cycle progression through ubiquitination of β-catenin [8]. Deletions of FAM46C have been found in a few cancers, including multiple myeloma [9], gastric cancer [10] and myeloma [11], and to be associated with a shorter overall survival.…”
Section: Introductionmentioning
confidence: 99%
“…Other potential regulators of LDHA include β-catenin, 31 which has been proposed to regulate MYC 32 and cyclin G2, 22 among others. As we have shown MYC to be regulated by FAM46B, and our previous study reported that FAM46B inhibits cell proliferation and cell cycle progression in prostate cancer through ubiquitination of β-catenin, 7 it is probable that FAM46B may regulate LDHA expression via the β-catenin /MYC signaling in prostate cancer. LDHA has been known to be involved throughout oncogenesis 33 particularly due to the increased energy needs of cancer cells.…”
Section: Discussionmentioning
confidence: 67%
“…6 FAM46B has been shown to reduce prostate tumor growth in an in vivo model through ubiquitination of β-catenin. 7 FAM46C has been found to have tumor-suppressing functions in multiple myeloma 8,9 as well as hepatocellular carcinoma. [10][11][12] Finally, FAM46D is a proposed cancer immunotherapy target.…”
Section: Introductionmentioning
confidence: 99%
“…34 In addition, β-catenin involved in the regulation of cell growth, cell cycle, and apoptosis. 35 Moreover, inhibition of β-catenin in cancer cells could suppress the cell cycle distribution via downregulating the expressions of Cyclin D1 and c-Myc. 35 Our data indicated that PTX had no effects on the expressions of βcatenin, c-Myc, and Cyclin D1 in SKOV3/PTX cells, whereas TET or combination treatment significantly downregulated the expressions of β-catenin, c-Myc and cyclin D1 in SKOV3/PTX cells, indicating that TET enhanced anti-tumor effect of PTX in SKOV3/PTX cells via inhibition the β-catenin/c-Myc/Cyclin D1 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%